2022
DOI: 10.3389/fninf.2022.861967
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the EEG Alpha-to-Theta and Theta-to-Alpha Band Ratios as Indexes of Mental Workload

Abstract: Many research works indicate that EEG bands, specifically the alpha and theta bands, have been potentially helpful cognitive load indicators. However, minimal research exists to validate this claim. This study aims to assess and analyze the impact of the alpha-to-theta and the theta-to-alpha band ratios on supporting the creation of models capable of discriminating self-reported perceptions of mental workload. A dataset of raw EEG data was utilized in which 48 subjects performed a resting activity and an induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…In detail, theta EEG power spectrum in the frontal, temporal, and occipital areas was higher during the most complex task conditions. An evaluation of the alpha-to-theta and the theta-to-alpha band rations were investigated as indexes of mental workload (Raufi and Longo, 2022 ). In details, authors demonstrated the richness of the information in the temporal, spectral and statistical domains extracted from these indexes for the discrimination of self-reported perceptions of mental workload over two task load conditions.…”
Section: Measuring Mental Workloadmentioning
confidence: 99%
“…In detail, theta EEG power spectrum in the frontal, temporal, and occipital areas was higher during the most complex task conditions. An evaluation of the alpha-to-theta and the theta-to-alpha band rations were investigated as indexes of mental workload (Raufi and Longo, 2022 ). In details, authors demonstrated the richness of the information in the temporal, spectral and statistical domains extracted from these indexes for the discrimination of self-reported perceptions of mental workload over two task load conditions.…”
Section: Measuring Mental Workloadmentioning
confidence: 99%
“…It will also serve as a layer of explainability, providing analysts with tools for explaining spatial and temporal dynamic of cognitive activation. The inferences of these models of cognitive load can be compared against other indexes such as the theta-to-alpha or alpha-to-theta band ratios [ 54 ], increasing their meaningfulness and validity. Eventually, studies can be devoted to the development of additional recurrent neural networks for understanding the temporal aspects of the high-level representations of cognitive activation, and establishing if there exist sequences, and their lengths, that are repetitive and recurrent over time.…”
Section: Discussionmentioning
confidence: 99%
“…State-of-the-art models manipulating EEG data often rely on frequency bands, such as the alpha or theta rhythms, deemed the alphabet for brain functions and mental state extraction. These have been individually used as cognitive load indicators [ 50 , 51 ], or aggregated together [ 21 , 52 , 53 , 54 ] because they have been shown to be sensitive to task difficulty manipulation, task engagement or memory load [ 55 , 56 ]. However, these approaches often discard some EEG bands in favour of other bands.…”
Section: State Of the Art In Cognitive Load Modelingmentioning
confidence: 99%
“…In recent years, deep learning methods have been developed to detect various neurological disorders that utilize EEG signals [15], [75] and solve various classification tasks [76], [77], [78]. Although these methods work well in finding hidden features and patterns from the nonlinear data, they struggle to attain higher-classification accuracy on EEG due to the data being highly complex and the frequent non-cerebral contamination that accompanies it [61], [62].…”
Section: B Motivationmentioning
confidence: 99%